Smartphone as Ritual Fan: Poaching in Weixin-mediated (Cyber)space with Nuosu-Yi Ritualists of Liangshan, Southwest China - Jan Karlach (Journal of Digital Social Research)
This article explores the engagement of the bimo – the Liangshan ethnic Nuosu-Yi literati-ritualists of Sichuan Province, China – with Weixin (WeChat), a ubiquitous Chinese all-in-one app. Utilizing a nethnographic approach – an ethnography of culturally conditioned simultaneous online and offline practices – I argue that by using the smartphones in ways unforeseen by their developers, the bimo are poaching the property of those who designed the app primarily for the Chinese-speaking majority. The usage of technology stipulated by the modernization push of the Chinese authoritarian state then transforms both the bimo and technology. The resultant techno-culture not only builds upon, reinvents, develops and reinforces the allegedly diminishing Nuosu-Yi folkways – especially inter-clan competition – but also feeds the state-approved Yi folklore. The dialogic reconciliation of the top-down computerization of society and the bottom-up socialization of technology reveals itself as intrinsically connected to the culturally conditioned use of technology in our everyday lives.